RESIKO DALAM PERJANJIAN MENGULANG SEWAKAN DAN AKIBAT HUKUMNYA - Yohan Lihu (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractCar rental service (four-wheeled) is a service company in the field of land transportation that receives its consumer orders, either for one destination or some destination by renting a car (four wheel) with the driver including fuel or just enough car (four wheel) its just fine. And also will always offer other service products to prospective customers.In a car lease agreement (four-wheeled) often repeat rent to another party due to the limited number of existing cars (wheels four) with the demand of tenants is high enough, so that renters often rent a car (four wheel) to rent again to the parties others to gain profit in meeting consumer demand.